GURU SEJAHTERA, KELAS BAHAGIA: TINJAUN PUSTAKA SISTEMATIS BERDASARKAN KESEJAHTERAAN GURU TERHADAP EFEKTIVITAS PEMBELAJARAN DI DALAM KELAS - Aryadi Aryadi; Achmad Supriyanto (Jurnal Manajemen Pendidikan, 2026)
This study aims to integrate empirical findings regarding the impact of teacher well-being on the effectiveness of the teaching-learning process and to map the mediating factors within this relationship. The method employed is a Systematic Literature Review (SLR) following the PRISMA guidelines through the stages of identification, screening, eligibility, and inclusion. A total of 40 articles from Google Scholar, ERIC, Scopus and DOAJ databases for the 2020-2025 period were analyzed in depth. The findings indicate that teacher well-being serves as the primary foundation for high-quality teacher-student relationships and the creation of a positive classroom climate that enhances student achievement. Conversely, low levels of well-being, particularly among honorary teachers due to unstable income, are proven to diminish teaching quality as focus is diverted to side occupations. The originality of this research lies in the profound exploration of the link between teachers' psychological conditions and concrete pedagogical practices, reinforcing the principle of "prosperous teachers, happy classrooms" as a pillar of the educational ecosystem. It is concluded that fulfilling teachers' human rights is an absolute prerequisite for teaching effectiveness. As a policy recommendation, governments and educational institutions must guarantee financial stability and psychological support for teachers to ensure professional sustainability and optimal national education quality.